2020
DOI: 10.3390/su13010073
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Strategies for the Use of Reflective Foils for Fruit Colouration to Reduce Plastic Use in Orchards

Abstract: (1) Background: Plastic in fruit orchards represents an environmental issue due to large CO2eq emissions associated with its production from fossil fuel and disposal (often incineration). (2) Materials and methods: Apple cv. “Braeburn Hillwell” trees on M9 rootstocks under a hail net were used at Campus Klein-Altendorf (CKA), Germany (50 °N) in 2018. In order to reduce the use of plastics to improve the red colouration of fruit particularly under hail nets, three alternatives to the current use of reflective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Satisfactory colour of apple fruit requires a certain amount of available sunlight. Therefore, fruit or fruit parts grown in shade will not turn red during ripening due to a lack of anthocyanin synthesis, particularly under hail nets [11,12]. This may be due to providing a longer exposure to light during the time, when anthocyanin synthesis, PAL activity and MYB 1 and MYB 10 gene expression in the apple peel starts ca.…”
Section: Fruit Colourationmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfactory colour of apple fruit requires a certain amount of available sunlight. Therefore, fruit or fruit parts grown in shade will not turn red during ripening due to a lack of anthocyanin synthesis, particularly under hail nets [11,12]. This may be due to providing a longer exposure to light during the time, when anthocyanin synthesis, PAL activity and MYB 1 and MYB 10 gene expression in the apple peel starts ca.…”
Section: Fruit Colourationmentioning
confidence: 99%
“…Fruit in the first pick are mostly from the outer and upper periphery of the tree canopy. Because the main influence of the reflective mulches can be observed and explained on fruit from the inner part of the tree canopy [12], their portion enhances in the first pick. Sometimes fewer picks have to be carried out to retrieve all fruit from a tree.…”
Section: Fruit Picksmentioning
confidence: 99%
“…Reflective mulches are mo in Washington State (US), Chile, and China and to a lesser extent in Sout and New Zealand (Figure 6). Sustainability aspect: In the search for sustainable alternatives to Extend et al (2021) [14] at Klein-Altendorf (University of Bonn) developed two so spreading of the reflective mulch in every other row; or (b) silver foil made aluminum. The authors' LCA showed savings in GHG emissions in the ord CO2e/ha.…”
Section: Reflective White (Or Silver) Mulchesmentioning
confidence: 99%
“…Partial defoliation originates from viticulture an more sustainable approach than plastic or aluminum (Figure 7). Sustainability aspect: In the search for sustainable alternatives to Extenday & Co., Hess et al (2021) [14] at Klein-Altendorf (University of Bonn) developed two solutions: (a) the spreading of the reflective mulch in every other row; or (b) silver foil made from recycled aluminum. The authors' LCA showed savings in GHG emissions in the order of 0.7-1.1 t CO 2e /ha.…”
Section: Reflective White (Or Silver) Mulchesmentioning
confidence: 99%
“…To be sustainable, an apple farm must produce adequate yields of high quality, be profitable, protect the environment, conserve resources, and be socially responsible in the long term [4,5]. For example, the use of plastic in apple orchards can be reduced by using the material several times in the same year or years, by using it in every other row, or by replacing it with another reflective material-an important step toward environmentally friendly, sustainable horticulture [6]. Thanks to the changes that have taken place in recent years in the field of image analysis methods and computational performance, it is possible to develop solutions for automatic fruit counting based on registered digital images and predict yield, which contributes to better planning of harvest [7].…”
mentioning
confidence: 99%